QUALIFICATIONS FRAMEWORKS LEADING TO REFORMS IN EAST EUROPEAN EDUCATION - Arjen Vos (Russian State Vocational Pedagogical University, 2015)
The paper examines the evolution of qualifications frameworks across Europe. Five years ago, it was not clear if the discussions on national qualification frameworks (NQF) in Eastern Europe would lead to the new standards and qualifications development, or initiate the reforms in education and training. Now, there is evidence of more countries using the NQFs to promote a dialogue between the public and private sectors on the expected outcomes of educational process. In some countries, the private sector has even taken the lead in the NQF discussions, being increasingly involved in their implementation. This is a fundamentally new paradigm in education policies and a cornerstone of the demand driven education and training. Each country is following its own patterns while moving to the comparable results. However, this is just the initial stage of NQF implementation. The author regards learning by doing and the local expertise expansion as the key challenges of the coming years. Although the reforms take time, they increasingly tend to become a shared public and private responsibility.